The Influence of Activity Complexity, Operational Efficiency, and Cost Structure on Cost Behavior : Study in PT Toyota Motor Manufacturing Indonesia 2022-2023 - Rahmawati, Dwi Yana; Isnawiyah, Isnawiyah; Maulaningrum, Pristiya; Layalia, Aghnia; Pandin, Maria Yovita R (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Cost behavior is a fundamental element in managerial accounting, because it affects decision making, planning, and cost control in an organization. This study aims to analyze the effect of activity complexity, operational efficiency, and cost structure on cost behavior in an organization at PT Toyota Motor Manufacturing Indonesia. Activity complexity indicates the diversity and interconnectedness of business processes that can increase indirect costs, while operational efficiency reflects the company’s ability to manage resources optimally. The cost structure that describes the proportion between fixed costs and variable costs also determines the sensitivity of costs to changes in activity. With a theoretical approach from modern cost management literature and managerial accounting, this article concludes that these three variables play an important role in shaping cost behavior, both individually and in an integrated manner. Proper integration of the three can help companies design adaptive and sustainable cost control strategies, especially in facing a dynamic business environment. This study recommends the application of an activity-based approach and operational efficiency for PT Toyota Motor Manufacturing Indonesia to improve the accuracy of cost planning and decision making